Application of an integrated loach-plant-substrate-microbes non-aerated saturated vertical flow constructed wetlands: Mechanisms of pollutants removal and greenhouse gases reduction. (January 2023) - Fu, Xiuzheng; Yu, Zhengda; Kong, Fanlong; Duan, Pingping; Li, Fanyi; Zhang, Lingzhu; Liu, Zhongying; Cui, Yuqian
Graphical abstract: Highlights: The system enhanced pollutants removal and reduced GHG emissions simultaneously. Loach facilitated oxygen transportation and pollutants conversion in sediment. Sufficient bioavailable carbon source promoted thorough denitrification. Loach enhanced the absorption of phosphorus by substrates and microorganisms. Abstract: This study established an integrated loach-plant-substrate-microbes non-aerated saturated vertical flow constructed wetlands (VFCWs) to enhance pollutants removal efficiencies and reduce greenhouse gas emissions simultaneously. The results of the VFCWs experiment indicated that the removal efficiencies of chemical oxygen demand, total phosphorous, and total nitrogen in loach systems were significantly higher than those of non-loach systems, achieving 59.16%, 35.98%, and 40.96%, respectively. The CH4 and N2 O emission fluxes were also significantly reduced in the integrated system, resulting in lower global warming potential (GWP) and GWP per unit of pollutants removal. Loaches promoted the transportation of oxygen, facilitated the re-contact and utilization of sediments, reduced CH4 emission, and enhanced nitrogen conversion and phosphorus accumulation. Increased bioavailable carbon and nitrate-nitrogen in the integrated system improved the abundance of denitrifying bacteria, which supported complete denitrification, reducing N2 O emissions with high pollutant removal.